2012
DOI: 10.1038/sc.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

Could motor imagery be effective in upper limb rehabilitation of individuals with spinal cord injury? A case study

Abstract: Study design: A case study. Objective: The aim was to investigate whether motor imagery (MI) could be successfully incorporated into conventional therapy among individuals with spinal cord injury (SCI) to improve upper limb (UL) function. Setting: The Physical Medicine and Rehabilitation Unit at the Henry Gabrielle Hospital in Lyon, France. Methods: The participant was an individual with a complete C6 SCI. MI content was focused on functional UL movements, to improve hand transport to reach out and grasp with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 21 publications
0
46
0
5
Order By: Relevance
“…MV was reduced in three SCI participants (≈70 %), whereas 81 % of increase was measured in one SCI subject. While we only focused on the tenodesis grasp, Grangeon et al (2012) reported reduced variability of hand trajectories during point-to-grasp actions after 5 weeks of rehabilitation with MI. Here, the baseline period was of equivalent duration to the intervention period in SCI participants with stabilized motor deficits.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…MV was reduced in three SCI participants (≈70 %), whereas 81 % of increase was measured in one SCI subject. While we only focused on the tenodesis grasp, Grangeon et al (2012) reported reduced variability of hand trajectories during point-to-grasp actions after 5 weeks of rehabilitation with MI. Here, the baseline period was of equivalent duration to the intervention period in SCI participants with stabilized motor deficits.…”
Section: Discussionmentioning
confidence: 96%
“…This was not expected for SCI subjects. MI training has been shown to improve movement speed during tenodesis actions, yet in single-case experimental designs (Grangeon et al 2012). Greater sample size in the present design should have enabled to detect meaningful effects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Adaptada de [32] Una de las grandes inquietudes que surge es si en efecto un proceso de rehabilitación apoyado con BCI invasiva puede restaurar funciones motoras. Al respecto, en un caso de estudio realizado en el año 2011 [8] se reporta que un paciente con lesión en C6 logró reducir el tiempo de realización del Test de Minnesota de destreza manual en 1 min y 25 s, demostrándose así que las BCI de imaginación motora pueden ser introducidas en procesos convencionales de rehabilitación a nivel de miembros superiores en pacientes con lesiones medulares. Recientemente, en un reporte científico en la revista Neurosurgery [3] se mostró el efecto de las BCI en procesos de rehabilitación física después de 12 meses de continuo trabajo con ocho pacientes con paraplejía completa, de los cuales 4 pacientes fueron posteriormente diagnosticados con paraplejía incompleta.…”
Section: Introductionunclassified
“…The validity of motor imagery has been proven in numerous studies which have investigated this technique and its neurophysiological basis in patients with spinal cord injuries5,6,7,8,9,10,11 ) . Grangeon et al10 ) showed that motor image training and general rehabilitation training in cervical injury patients improved their score in the performance of hand function tasks and also shortened performance time, thus demonstrating that motor image treatment and general rehabilitation treatment are effective when conducted together. However, because study of Grangeon et al10 ) has been conducted case study of cervical patients, it is a difficult to generalize.…”
Section: Introductionmentioning
confidence: 99%